2020
DOI: 10.20473/mgi.v15i1.7-13
|View full text |Cite
|
Sign up to set email alerts
|

PERBANDINGAN LINGKAR BETIS DAN LINGKAR LENGAN ATAS SEBAGAI UKURAN PENGGANTI BERAT LAHIR <br><i> [Comparison between Calf and Mid-Upper Arm Circumference Alternative of Birthweight Measurement]</br></i>

Abstract: High proportion of unmeasured birth weight as well as its improper documentation has become a problem in developing countries, including Indonesia. In 2017, a total of 9.9% labour were not assisted by health personnel and 43.4% of newborn did not have proper birth record. This condition increases the possibility of undetected low birth weight (LBW) cases. Therefore, this study aimed to determine an alternative measurement of birth weight which able to detect LBW. The study used cross sectional approach to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Our results also harmonize with a study conducted by Putra et al (2020), which focused on a maternity clinic in Jakarta. This study found a significant relationship between calf circumference and upper arm circumference with birth weight (p<0.001), with correlation coefficients (r values) of 0.529 and 0.674, respectively.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our results also harmonize with a study conducted by Putra et al (2020), which focused on a maternity clinic in Jakarta. This study found a significant relationship between calf circumference and upper arm circumference with birth weight (p<0.001), with correlation coefficients (r values) of 0.529 and 0.674, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Additionally, the PPV was 8.2%, the NPV was 98.9%, the likelihood ratio (+) was 31.7, and the likelihood ratio (-) was 0.03. Notably, this research indicated that calf circumference performed better as a surrogate measure for birth weight in identifying low birth weight neonates when compared to measurements of upper arm circumference (Putra et al, 2020).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation